2020
DOI: 10.1007/s00126-020-00987-5
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the Flatreef deposit, northern Bushveld, by hydrodynamic and hydromagmatic processes

Abstract: New lithological and whole rock compositional data show that the main platinum-group element (PGE) horizons of the Flatreef succession show strong compositional similarities to the Merensky and Bastard reefs of the western Bushveld Complex (WBC), notably in terms of many immobile and incompatible minor and trace elements such as TiO 2 , Zr, Y, and REE. However, Al 2 O 3 , CaO, and Na 2 O contents are markedly lower in the Flatreef, whereas MgO contents are higher. In view of broadly similar silicate mineral co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Since the discovery of PGEs in the Bushveld Complex (Cawthorn, 1999;Scoon and Mitchell, 2004), the bulk of research efforts on this layered intrusion up until the rst decade of the 21st century concentrated on the western and eastern lobes of the intrusion (Eales and Cawthorn, 1996;Cawthorn, 2015). The northern lobe, however, has witnessed a surge in both mining activity and research, particularly for PGEs, since the rst decade of this century (e.g., Scoon et al, 2020;Maier et al, 2021;Yudovskaya et al, 2022). Cawthorn and Walraven (1998) concluded that during emplacement and fractional crystallization of the Bushveld Complex, the intrusion experienced initial temperatures of ca.…”
Section: Brief Outline Of the Geology Of The Bushveld Complex And The...mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the discovery of PGEs in the Bushveld Complex (Cawthorn, 1999;Scoon and Mitchell, 2004), the bulk of research efforts on this layered intrusion up until the rst decade of the 21st century concentrated on the western and eastern lobes of the intrusion (Eales and Cawthorn, 1996;Cawthorn, 2015). The northern lobe, however, has witnessed a surge in both mining activity and research, particularly for PGEs, since the rst decade of this century (e.g., Scoon et al, 2020;Maier et al, 2021;Yudovskaya et al, 2022). Cawthorn and Walraven (1998) concluded that during emplacement and fractional crystallization of the Bushveld Complex, the intrusion experienced initial temperatures of ca.…”
Section: Brief Outline Of the Geology Of The Bushveld Complex And The...mentioning
confidence: 99%
“…An understanding of ore formation in the northern lobe of has been made more complex, however, due a variety of factors such relatively poor outcrop as well as contamination of Bushveld Complex magmas with country rocks (Buchanan et al, 1981;Buchanan and Rouse, 1984;Cawthorn et al, 1985;Armitage et al, 2002). The occurrence of abundant footwall rafts and xenoliths, together with the disturbance of magmatic stratigraphy in the northern lobe bear testimony to the uniqueness of northern lobe rocks in comparison to those of the western and eastern lobes of the Bushveld Complex (Maier et al, 2021). The discovery of the Flatreef in the southern sector of the northern lobe permitted correlations with other lobes of the Bushveld Complex (Kruger, 1994;Roelofse et al, 2015) through the study of a magmatic stratigraphy less affected by footwall interaction such as strontium isotope ratios (Beukes et al, 2020), for example, and also with the northern sectors of the northern lobe (Buchanan et al, 1981;Gain and Mostert, 1982;Buchanan and Rouse, 1984;Yudovskaya et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The efforts of the organizing committee in carrying out field excursions and coreyard visits are gratefully acknowledged. Maier et al (2020) focus on the petrogenesis of the most highly mineralized portion of the Flatreef, namely, the interval between the MZ and the base of the Merensky Reef. Based on a detailed examination of four drill cores, they propose that the combination of several favourable processes, including country rock assimilation as well as hydrodynamic and hydromagmatic processes, resulted in exceptionally thick mineralized intervals (e.g.…”
Section: Contributions In This Thematic Issuementioning
confidence: 99%
“…The Flatreef mineralised zone is interpreted as the down-dip extension of the Platreef (Kekana 2014;Grobler et al 2019;Maier et al 2021Maier et al , 2023. A recent stratigraphic interpretation for the Flatreef on the farms Turfspruit and Macalacaskop by Grobler et al (2019) strengthens its correlation to the Critical Zone as found elsewhere in the Bushveld Complex, but suggests that the Flatreef is controlled by a distinctive structural style, the origin of which is not yet determined.…”
Section: Introductionmentioning
confidence: 99%
“…Ore-forming processes in magmatic orebodies are affected by their structural evolution (e.g. Clarke et al 2000Clarke et al , 2005Saumur and Cruden 2017;Maier et al 2021), which also affects post-intrusion deformation of ore bodies. Studies mentioning the structure of the Northern Limb have been made at the scale of open pit outcrops (e.g.…”
Section: Introductionmentioning
confidence: 99%